MENJADI ORANG TUA EFEKTIF (MENINGKATKAN PRESTASI BELAJAR ANAK) - Sahadir Sahadir (FORUM PAEDAGOGIK, 2018)
In learning experience of children at home, of cource the role of parents is very crucial as a leader, educator, and motvator. In this entexct, parents must be motvated, and controlled ad activities of children in order to gain the efective learning in any time. This article presented to describe to become the effective parents.